Asymmetric Aldol Reaction of Pyruvate Promoted by Chiral Tertiary Amines. Issue 25 (1st July 2020) - Pasternak‐Suder, Monika; Pacułt, Wojciech; Baś, Sebastian; Mlynarski, Jacek
Abstract: The direct asymmetric aldol reaction of α‐ketoesters catalyzed by chiral tertiary amines is reported. The described methodology is characterized by mild reaction conditions and distinct product selectivity determined by the starting materials. In the developed transformation pyruvates undergo highly selective self‐condensation reaction, whereas cross‐aldol reaction take place predominantly for their carbon chain homologues in presence of aldehyde acceptors. Notably, addition of bulky phenol moiety into pyruvate inhibit the spontaneous lactonization of products and enhance the enantioselectivity. Abstract : The direct asymmetric aldol reaction of α‐ketoesters catalyzed by chiral tertiary amines is performed. Difference in the reactivity between pyruvate (R 1 =H) and its homologues (R 1 ≠H) has been observed. Pyruvate undergoes a homo‐aldol reaction exclusively resulting in high enantioselectivity depending on ester type (Ar‐bulky group). Whereas, higher α‐ketoesters (R 1 ≠H) prefer to react with aldehydes affording acceptable yields and moderate enantioselectivities.